Quadrature differential output six‐port rat‐race coupler - Michihiro Harada; Hitoshi Hayashi (Electronics Letters, 2021)
Abstract This letter describes a design method for a six‐port rat race circuit to obtain quadrature differential waveforms from a single end. The proposed six‐port rat‐race coupler succeeded in low insertion loss and wide bandwidth by using a 1/2 wavelength transmission line and an open stub. Over the frequency range from 0.89 to 1.05 GHz, a prototype 0.96‐GHz‐band six‐port rat‐race coupler was confirmed to have a transmission loss of 7.03  ±  0.45 dB, a reflection loss and isolation of 15 dB or more, and a phase error of within ± 3.3 ○.